Thai men becoming a first-time father - Nantaporn Sansiriphun (2018)
The purpose of this study was to understand the process of Thai men becoming a first-time father. Twenty expectant fathers were voluntarily recruited from the antenatal clinics of three hospitals in Chiang Mai, northern Thailand. The data were collected by in-depth interviews and analyzed on the basis of grounded theory methodology. The findings demonstrated that "protecting the unborn baby" was the basic social process that emerged as the core category. This process was divided into three phases: confirming and accepting, perceiving the unborn baby as a human being, and ensuring the health of the mother and baby. Throughout this process, the Thai expectant fathers applied many strategies to manage their concerns, needs, and emotions and to develop themselves into fathers. The process of protecting the unborn baby provides insight into the expectant fathers' experiences, which will enable nurses and midwives to assist and care for men as they become fathers. © 2010 Blackwell Publishing Asia Pty Ltd.